12(S)‐hydroxyeicosatetraenoic acid impairs vascular endothelial permeability by altering adherens junction phosphorylation levels and affecting the binding and dissociation of its components in high glucose‐induced vascular injury. Issue 3 (24th October 2018) - Wang, Xiaofang; Gao, Lu; Xiao, Lili; Yang, Lulu; Li, Wenshu; Liu, Gangqiong; Chen, Linlin; Zhang, Jinying
Abstract: Aims/Introduction: Diabetes is an important risk factor for atherosclerotic disease. The initiating factor of atherosclerosis is local endothelial cell injury. The arachidonic acid metabolite, 12(S)‐hydroxyeicosatetraenoic acid (12[S]‐HETE), might be involved in this process. In recent years, some studies have discussed the effect of 12(S)‐HETE on vascular endothelial cell function. In the present study, we investigated the effect of 12(S)‐HETE on vascular endothelial cell function in high‐glucose conditions and the mechanisms involved. Materials and Methods: Human umbilical vein endothelial cells were cultured in conventional M199 medium and high‐glucose M199 medium. Human umbilical vein endothelial cells were stimulated with 12(S)‐HETE and cinnamyl‐3, 4‐dihydroxy‐α‐cyanocinnamate (a 12/15‐lipoxygenases inhibitor). A type 1 diabetes mellitus model was established in C57BL/6 or 12/15‐lipoxygenases knockout mice with streptozotocin. Aortic tissue was harvested for subsequent testing. The transmembrane transport of dextran and human acute monocytic leukaemia cell line (THP‐1) cells was measured. The adherens junction protein, IkBα, nuclear factor kappa Bp65 (P65), intercellular adhesion molecule 1 and vascular cell adhesion protein 1 expression and phosphorylation, and the binding/dissociation of endothelial cell components were observed. Results: Transendothelial migration of dextran and THP‐1 cells was significantly increased by stimulation of human umbilical vein endothelial cell monolayers with high glucose and 12(S)‐HETE ( P  < 0.05). High glucose and 12(S)‐HETE altered the vascular endothelial cadherin and β‐catenin phosphorylation level, and promoted the dissociation of β‐catenin and vascular endothelial cadherin. Expression levels of P‐Ikbα, P‐P65, intercellular adhesion molecule 1 and vascular cell adhesion protein 1 were elevated in high glucose and 12(S)‐HETE treated cells and diabetic mice compared with controls ( P  < 0.05). Conclusions: The lipoxygenases metabolite, 12(S)‐HETE, can impair vascular endothelial permeability by altering adherens junction phosphorylation levels, and affecting the binding and dissociation of its components in high‐glucose conditions. Abstract : The LO metabolite 12(S)‐HETE can impair vascular endothelial permeability by altering adherens junction phosphorylation levels and affecting the binding and dissociation of its components in high‐glucose conditions.